2020
DOI: 10.1017/cjn.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Access to Stroke Care Services in Rural Communities in Ontario, Canada

Abstract: ABSTRACT:Background:Optimal stroke care requires access to resources such as neuroimaging, acute revascularization, rehabilitation, and stroke prevention services, which may not be available in rural areas. We aimed to determine geographic access to stroke care for residents of rural communities in the province of Ontario, Canada.Methods:We used the Ontario Road Network File database linked with the 2016 Ontario Acute Stroke Care Resource Inventory to estimate the proportion of people in rural communities, def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The ability to clearly locate specific population groups provides the opportunity to identify risk areas in preventive research. The effects of different population distributions reinforce previous findings on inequality in medical care [ 28 , 53 ]. Thus, we show that a multitemporal view of the population distribution can produce variations in the accessibility situation in the same way as the use of different speed scenarios.…”
Section: Discussionsupporting
confidence: 86%
“…The ability to clearly locate specific population groups provides the opportunity to identify risk areas in preventive research. The effects of different population distributions reinforce previous findings on inequality in medical care [ 28 , 53 ]. Thus, we show that a multitemporal view of the population distribution can produce variations in the accessibility situation in the same way as the use of different speed scenarios.…”
Section: Discussionsupporting
confidence: 86%
“…Social demographics such as socioeconomic status, sex, geographic location, income, and education are still important factors affecting the accessibility of health services, especially in rural areas [46]. Previous studies in Canada have suggested that rural residents have reduced access to basic stroke care, such as computed tomography, thrombolysis, a stroke unit, a stroke prevention clinic, or inpatient rehabilitation once they have had a stroke, and therefore experience relatively more severe outcomes, including disability [47,48]. Our study also found that dialysis patients living in severely affected areas had a higher risk of mortality than patients in moderately affected areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown how much this would influence our data given that MRI is more costly and time-consuming in the acute setting compared to CT imaging and is not widely available across the province. 44 The effect of the tissue-based definition on TIA diagnoses will therefore depend on both the timing of clinical evaluation and access to DWI. 45 There was a significant amount of missing data on MRI utilization in our study, which hindered our ability to examine the potential impact of MRI on TIA diagnoses.…”
Section: Discussionmentioning
confidence: 99%